Motives for volunteering in sport organisations and the relationship with volunteer commitment and volunteer satisfaction - Tshabalala, Lebamang Francis (Vaal University of Technology, 2022)
Volunteering is a core component of sport service delivery and remains essential to the viability of the sport system in many sport organisations and communities. To this end, it has become incumbent for them to ensure that a sufficient pool of volunteers exists. Despite this assertion that volunteers in sport organisations are considered such a valuable resource, they are increasingly scarce and there is a considerable debate about the underlying structure or dimensionality of volunteer motives. Therefore, the primary objective of this study was to examine motives for volunteering in sport organisations within Gauteng province and its relationships with volunteer commitment and volunteer satisfaction. This research drew from the convergence of the social exchange and self-determination theories that were used in this study to provide a theoretical understanding as to why people engage in volunteer work and the outcomes thereof. In order to achieve the primary objective of the study, a quantitative research approach was adopted and a cross-sectional descriptive survey was utilised. A non-probability convenience sampling procedure was also adopted. Prior to the main survey data collection, a pilot study was undertaken by administering a questionnaire to 40 participants who did not form part of the main survey. The main survey data was thereafter acquired from 270 volunteers from conveniently selected sport organisations within Gauteng province through a structured self-administered questionnaire. The data were analysed using the Statistical Package for the Social Science (SPSS version 26.0) and the reliability and validity analysis yielded satisfactory results in terms of the measuring instrument. Descriptive statistics were also computed to summarise the data into usable information by making use of frequencies, means and standard deviations. Exploratory factor analysis was used to statistically aggregate the large number of observed measures (28 items) relating to independent variable (volunteer motives) into a smaller set of three unobserved (latent) variables called factors while regression and correlation analysis were undertaken to establish the relationships among the study constructs in line with the objectives of the study. Results fromcorrelation and regression analysis respectively (r = 0.440; β= .410) revealed that volunteer motives significantly contribute towards enhancing volunteer commitment among volunteers in sport organisations. Furthermore, the study’s results indicated that volunteer commitment, in turn, contributes towards volunteer satisfaction of volunteers in sport organisations (r = 0.561; β= .561). Based on these results, this study recommends, among others, that management of sport organisations should explore the effectiveness of implementing an internal system of self-evaluation as a starting point to examine motives for volunteering. Furthermore, it is recommended that sport organisation management should develop an organisational culture which assigns authority and responsibility to sport volunteers. The study concludes by affirming the achievement of the study’s objectives, highlighting its limitations as well as identifying future research opportunities.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Sport organisations; Volunteering; Volunteer motives; Volunteer commitment; Volunteer satisfaction; Dissertations, Academic -- South Africa.; Sports administration -- South Africa.; Sports -- Social aspects -- South Africa.; Voluntarism.